2011
DOI: 10.1038/emboj.2011.399
|View full text |Cite
|
Sign up to set email alerts
|

An interspecies analysis reveals a key role for unmethylated CpG dinucleotides in vertebrate Polycomb complex recruitment

Abstract: The role of DNA sequence in determining chromatin state is incompletely understood. We have previously demonstrated that large chromosomal segments from human cells recapitulate their native chromatin state in mouse cells, but the relative contribution of local sequences versus their genomic context remains unknown. In this study, we compare orthologous chromosomal regions for which the human locus establishes prominent sites of Polycomb complex recruitment in pluripotent stem cells, whereas the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 44 publications
15
162
2
2
Order By: Relevance
“…Additionally, we demonstrate that DNA methylation inhibits H3K27me3 deposition at CpG-rich sequences and that this inhibition can be reversed upon chemical removal of DNA methylation. These observations readily explain the occupancy of H3K27me3 and DNA methylation observed throughout the genome (23,24,33,34). They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Additionally, we demonstrate that DNA methylation inhibits H3K27me3 deposition at CpG-rich sequences and that this inhibition can be reversed upon chemical removal of DNA methylation. These observations readily explain the occupancy of H3K27me3 and DNA methylation observed throughout the genome (23,24,33,34). They extend previous studies that already suggested a role for CpG dinucleotides in PRC2 recruitment (22,23) but are also more comprehensive and provide novel mechanistic details.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, loss of Polycomb recruitment coincides with increased susceptibility to DNA methylation. This finding is compatible with the observation of increased H3K27 methylation upon global loss of DNA methylation (23,24,33,34), which we also observe in our genome-wide datasets (Fig. S7A).…”
Section: Dna Methylation and H3k27me3 Recruitment Exclude Each Other Atsupporting
confidence: 92%
See 2 more Smart Citations
“…histone deacetylases (HDACs) and another repressive Polycomb complex (called PRC1) (Lynch et al 2012). Experimental data suggest that together, these complexes (PRC1, PRC2, and HDACs) maintain the silence of the a genes in multipotent cells and differentiated nonerythroid cells Lynch et al 2012) but that they are cleared from the a-globin promoter before the activation steps described (see Fig.…”
Section: Dr Higgsmentioning
confidence: 99%